Survey of Professionals of the European Public Health Association (EUPHA) towards Direct-to-Consumer Genetic Testing. (30th September 2022) - Beccia, Flavia; Hoxhaj, Ilda; Sassano, Michele; Stojanovic, Jovana; Acampora, Anna; Pastorino, Roberta; Boccia, Stefania
Abstract: Background: The increasing availability of Direct-to-Consumer Genetic Tests (DTC-GTs) has great implications for public health (PH) and requires literate healthcare professionals to address the challenges they pose. We designed and conducted a survey to assess the state of knowledge, attitudes and behaviours of PH professionals members of the European Public Health Association (EUPHA) towards DTC-GTs. Methods: EUPHA members were invited to participate and fill in the survey. We performed multivariable logistic regression to evaluate associations between selected covariates and knowledge, attitudes and behaviours of healthcare professionals towards DTC-GT. Results: Three hundred and two professionals completed the survey, 66.9% of whom were not involved in genetics or genomics within their professional activities. Although 74.5% of respondents were aware that DTC-GTs could be purchased on the web, most of them reported a low level of awareness towards DTC-GTs applications and regulatory aspects. The majority did not approve the provision of DTC-GTs without consultation of a healthcare professional (91.4%), were doubtful about the test utility and validity (61%) and did not feel prepared to address citizens' questions (65.6%). Predictors of knowledge on DTC-GT were the involvement in genetics/genomics and receiving training during the studies ( P < 0.0001 and P = 0.043). Predictors of attitudes were medical degree and knowledge about DTC-GTs ( P = 0.006 and P = 0.027). Conclusions: Our results revealed a high level of awareness of DTC-GT web purchasing and a moderate to low level of awareness towards their applications. Despite the overall positive attitudes, PH professionals reported a high need for strengthening regulatory aspects of DTC-GTs provision process.